Unique barium datasets improve our understanding of oceanic carbon storage. (Research'eu results magazine)
The West Antarctic Peninsula (WAP)'s high sensitivity to climate change makes it a perfect location for furthering scientific understanding of ocean chemistry. An EU-funded project is pursuing this objective with a focus on barium (Ba), which can provide a unique insight into both organic and inorganic carbon storage.